Precursory signatures in the visibility graph analysis of seismicity: An application to the Kachchh (Western India) seismicity. (2015) - Telesca, Luciano; Lovallo, Michele; Aggarwal, S.K.; Khan, P.K.
Highlights: The Visibility Graph (VG) was applied to Kachchh seismicity from 2003 to 2012. The k–M slope increases significantly before the occurrence of the largest shock. The VG method could be promising for the detection of seismic precursors. Abstract: The Visibility Graph (VG) method maps time series into networks or graphs, converting dynamical properties of time series in topological properties of networks. The VG method was applied to the aftershock depleted catalogue of the Kachchh Gujarat (Western India) seismicity from 2003 to 2012, in order to identify possible precursory signatures in the pattern of the VG parameters. The k–M slope (the slope of the line fitting the relationship between the magnitude of the events and their connectivity degrees) seems to sharply increase significantly before the occurrence of the largest shocks ( M ⩾ 4.5) of the sequence.